Modulation of angiogenic vascular endothelial growth factor by tumor necrosis factor alpha and interleukin-1 in rheumatoid arthritis. - Paleolog, E; Young, S; Stark, A; McCloskey, R; Feldmann, M; Maini, R (1998)
OBJECTIVE: To investigate the regulation of expression of the angiogenic cytokine vascular endothelial growth factor (VEGF) in rheumatoid arthritis (RA), in order to determine whether new blood vessel formation could be a potential therapeutic target in RA. METHODS: Dissociated RA synovial membrane cells were cultured in the presence of cytokine inhibitors, or under hypoxic conditions. Serum VEGF levels were serially measured in RA patients enrolled in clinical trials of anti-tumor necrosis factor alpha (anti-TNFalpha) monoclonal antibody treatment. RESULTS: Combined neutralization of TNFalpha and interleukin-1 (IL-1) in RA synovial membrane cultures reduced VEGF release by 45% (P < 0.05 versus control), although blockade of either TNFalpha or IL-1 activities alone resulted in only small inhibitory effects. In addition, release of VEGF from RA synovial membrane cells was selectively up-regulated by hypoxia. Serum VEGF levels were significantly elevated in RA patients relative to control subjects, and correlated with disease activity. Treatment of RA patients with anti-TNFalpha significantly decreased serum VEGF, and this effect was enhanced by cotreatment with methotrexate. CONCLUSION: Inhibition of TNFalpha and IL-1 activity in vivo could reduce the drive to new blood vessel formation, and hence pannus mass, adding to other therapeutic effects of anti-TNFalpha therapy in RA.